Answer:
Exponential decay
Step-by-step explanation:
b = 0.73
Since the b is less than 1 (b<1), the rate is decreasing.
Alan's dogs have a total of 24 legs (l). If each dog has 4 legs, which equation gives the number of dogs (d) that Alan has?
Answer: 24/4=D
Step-by-step explanation:
24LEGS/4LEGS=6DOGS
Answer:
4d=24
Step-by-step explanation:
4(dogs)=24 legs
so the answer is 6 dogs (in case you need it)
What are the solutions to x2 + 8x + 7 = 0?
A.x= -8 and x = -7
B.x=-7 and x = -1
C.x= 1 and x = 7
D.x= 7 and x = 8
Answer:
B
Step-by-step explanation:
x² + 8x + 7 = 0
x²+x+7x+7=0
x(x+1)+7(x+1)=0
(x+1)(x+7)=0
Either x=-1or x=-7.
solutions to equation x^2 + x - 30 = 12 using zero product property
Answer:
Our solutions are x= -7 , x=6
Step-by-step explanation:
x²+x-30=12
First we calculate the constants:
x²+x-30-12=0
x²+x-42=0
Now split the middle term:
x²+7x-6x-42=0
x(x+7)-6(x+7)=0
(x+7)(x-6)=0
As we know that:
a.b=0
⇒either a=0 or b=0
(x+7)=0 , (x-6)=0
x=0-7 , x=0+6
x= -7 , x=6
So our solutions are x= -7 , x=6....
You put $280 in a one-year CD that will earn 4.5% a year, calculated semiannually. How much simple interest will you earn?
Answer:
25.77 dollars
Step-by-step explanation:
280 × .045 = y
y + 280 = z
z × .045 = c
z + c = d
d - c = the answer. $25.77
A small bat weighs about 2/5 of an ounce. A small hummingbird weighs about 14/25 of an ounce. Explain how to find the difference in the weights of these animals
Answer:
The difference is about [tex]\frac{4}{25}[/tex] of an ounce
Step-by-step explanation:
we know that
A small bat weighs about 2/5 of an ounce
A small hummingbird weighs about 14/25 of an ounce
step 1
Multiply 2/5 by 5/5
Remember that
5/5 is 1
so
[tex](\frac{2}{5})(\frac{5}{5})=\frac{10}{25}[/tex]
step 2
To find the difference in the weights of these animals, subtract the weight of the small bat from the weight of the small hummingbird
[tex](\frac{14}{25})-(\frac{10}{25})[/tex]
Remember that
When subtract fractions with the same denominators, subtract the top numbers and put the answer over the same denominator
so
[tex](\frac{14}{25})-(\frac{10}{25})=\frac{4}{25}[/tex]
therefore
The difference is about [tex]\frac{4}{25}[/tex] of an ounce
Which expression is equivalent to 6^-3?
6^3
3^6
3sqrt6
(1/6)^3
For this case we must find an expression equivalent to[tex]6 ^ {- 3}[/tex]
By definition of power properties we have to:
[tex]a ^ {- 1} = \frac {1} {a ^ 1} = \frac {1} {a}[/tex]
So, we can rewrite the given expression as:
[tex]6 ^ {3} = \frac {1} {6 ^ 3}[/tex]
This is equivalent to:
[tex](\frac {1} {6}) ^ 3[/tex]
Answer:
Option D
Answer:
The correct answer option is D. ( 1 / 6 ) ^ 3.
Step-by-step explanation:
We are given the following expression and we are to determine whether which of the given answer options is equivalent to this:
[tex] 6 ^ { - 3 } [/tex]
Rewriting this as a fraction to get:
[tex] \frac { 1 } { 6 ^ 3 } [/tex]
Therefore, the correct answer option is D. ( 1 / 6 ) ^ 3.
what’s the value of y ?
hey! the value of y is 57
Which statements are true regarding the prism? Check
all that apply.
The prism has no vertices.
The prism has 9 edges.
The bases of the prism are triangles.
The bases of the prism are rectangles.
The prism has 5 faces.
O
Answer:
1. The base is a triangle.
Step-by-step explanation: This one seems like it's the only corret one, You might have to wait and see the other answers roll in.
Answer:
2,3&5
Step-by-step explanation:
got it right on edg 2020
the first two steps in determining the solution set of the system of equations y=x^2-6x
+12 and y=2x-4. Which represents the solution(s) of this system of equations?
For this case we have the following system of equations:
[tex]y = x ^ 2-6x + 12\\y = 2x-4[/tex]
Equating the equations:
[tex]x ^ 2-6x + 12 = 2x-4\\x ^ 2-6x-2x + 12 + 4 = 0\\x ^ 2-8x + 16 = 0[/tex]
We look for two numbers that when multiplied, get 16, and when added together, get -8.
These numbers are -4 and -4.
[tex](x-4) (x-4) = 0\\(x-4) ^ 2 = 0[/tex]
So, the solution is[tex]x = 4[/tex]
We look for the value of y:
[tex]y = 2x-4\\y = 2 (4) -4\\y = 8-4\\y = 4[/tex]
Finally, the solution is:[tex](4,4)[/tex]
ANswer:
[tex](4,4)[/tex]
3 sin^{2} x +cos 2x= (5/4)
answer in radians
Answer:
I believe it's 0.540717
Step-by-step explanation:
3(sin(2))x+(cos(2))(x)=5/4
Simplify: 2.311745x=5/4
Divide: 2.311745x/2.311735=5/4/2.311745
x=0.540717
Which line contains the point (2,1)
4x-y=7
2x+5y=4
7x-y=15
X+5y=21
Answer:
4x - y = 7.
Step-by-step explanation:
We substitute for x and y and see if they fit.
4x - y = 7
4(2) - 1 = 7
So it is the first line.
Answer: First option.
Step-by-step explanation:
To find which line contains the point (2,1), we can substitute the coordinates into each equation of the line provided in the options:
First option:
[tex]4x-y=7\\4(2)-1=7\\7=7[/tex]
It contains the point (2,1)
Second option:
[tex]2x+5y=4\\2(2)+5(1)=4\\9\neq 4[/tex]
It does not contain the point (2,1)
Third option:
[tex]7x-y=15\\7(2)-1=15\\13\neq15[/tex]
It does not contain the point (2,1)
Fourth option:
[tex]x+5y=21\\2+5(1)=21\\7\neq 21[/tex]
It does not contain the point (2,1)
The height of the parallelogram, h, can be found by dividing the area by the length of the base. If the area of the parallelogram is represented by 4x2 – 2x + 5 and the base is 2x – 6, which represents the height? 2x + 5 + 2x – 7 – 2x – 7 + 2x + 5 –
Answer:
[tex]\frac{4x^{2}-2x+5}{2x-6} =2x + 5 + \frac{35}{2x-6}[/tex]
Step-by-step explanation:
We know that the height of a parallelogram can be found by divind the area by the lenght of the base.
The area is 4x2 – 2x + 5 and the base is 2x – 6. To find the height, we need to divide both polynomials:
[tex]\frac{4x^{2}-2x+5}{2x-6} =2x + 5 + \frac{35}{2x-6}[/tex]
Answer:
[tex]2x+5+\frac{35}{2x-6}[/tex]
Step-by-step explanation:
Given,
The area of the parallelogram, A = [tex]4x^2-2x+5[/tex]
The length of its base, b = [tex]2x-6[/tex]
∵ The height of the parallelogram.
[tex]h=\frac{A}{b}[/tex]
[tex]\implies h=\frac{4x^2-2x+5}{2x-6}[/tex]
[tex]=2x+5+\frac{35}{2x-6}[/tex] ( by long division shown below )
Hence, the height of the given parallelogram is,
[tex]2x+5+\frac{35}{2x-6}[/tex]
An object is launched from a platform.
Its height (in meters), x seconds after the launch, is modeled by
h(x)=-5(x+1)(x-9)
What is the height of the object at the time of launch?
_________ meters
Please answer as soon as possible please!
Answer:
45 meters
Step-by-step explanation:
If x represents the seconds after the launch, then the time of launch is when x=0 so you just need to solve for h(0)
h(0) = -5(1)(-9)
h(0) = 45
Answer:
45 m
Step-by-step explanation:
At the time of launch, the time x = 0
Substitute x = 0 into h(x)
h(0) = - 5 (0 + 1)(0 - 9) = - 5(1)(- 9) = - 5 × - 9 = 45
Suppose line n has a slope of 5/7 and passes through (4,8). what is the equation for n in point-slope form?
Answer:
[tex]\large\boxed{y-8=\dfrac{5}{7}(x-4)}[/tex]
Step-by-step explanation:
The point-slope form of an equation of a line:
[tex]y-y_1=m(x-x_1)[/tex]
m - slope
We have the slope [tex]m=\dfrac{5}{7}[/tex] and the point [tex](4,\ 8)[/tex].
Substitute:
[tex]y-8=\dfrac{5}{7}(x-4)[/tex]
how do you calculate the median and mean of X based on the table?
Answer:
The mean is all the #s added up and divided by 5, and median is the number in the middle which is 0.18
Step-by-step explanation:
PLZ vote me for BRAINILEST
h(x) = 3x - 4
What is h(6)?
ETĀ. 14
e c. 22
SUBMIT
[tex]h(6)=3\cdot6-4=14[/tex]
Answer:
a. 14 is your answer.
Step-by-step explanation:
h(x) = 3x - 4
h(6) = ?
Plug in 6 for x: x = 6
h(6) = 3(6) - 4
Remember to follow PEMDAS. First, multiply, then subtract:
h(6) = (3 * 6) - 4
h(6) = (18) - 4
Simplify:
h(6) = 18 - 4
h(6) = 14
a. 14 is your answer.
~
If f(x)=-2x-3 find f(4)
Answer:
f(4) = -11
Step-by-step explanation:
Plug in 4 for x: Note that x = 4.
f(x) = -2x - 3
f(4) = -2(4) - 3
Remember to follow PEMDAS. First, solve the multiplication, then subtract:
f(4) = (-2 * 4) - 3
f(4) = (-8) - 3
f(4) = -11
f(4) = -11 is your answer.
~
A wall is 15 ft. high and 10 ft. from a house.
Find the length of the shortest ladder which
will just touch the top of the wall and reach a
window 20.35 ft. above the ground.
Answer:
=11.35 ft.
Step-by-step explanation:
The ladder, the flat surface the wall and the height up to the window form a trapezium.
The triangle that constitutes of the trapezium has the ladder as the hypotenuse, the distance between the two walls as base and the perpendicular distance from the base of the ladder to the window as height.
The height=20.35 ft-15 ft= 5.35 ft
Distance between the walls=10 ft
Hypotenuse²= base²+height²
H²=b²+h²
=10²+5.35²
=128.6225
H=√128.6225
=11.35 ft.
Answer:
11.41 ft
Step-by-step explanation:
Same steps as the other guy but, I have the correct answer(especially for Acellus)
find the value of x if A, B and C are collinear points and B is between A and C. AB= 6x, BC= x-5, AC= 23
Answer:
x=4
Step-by-step explanation:
AB + BC = AC
AB= 6x, BC= x-5, AC= 23
Substituting what we know
6x + x-5 = 23
Combine like terms
7x -5 = 23
Add 5 to each side
7x-5+5 =23+5
7x = 28
Divide each side by 7
7x/7 = 28/7
x=4
Find the distance between the points (–9, 0) and (2, 5).
Answer:
sqrt( 146)
Step-by-step explanation:
To find the distance between two points, we use the formula
d = sqrt( ( y2-y1)^2 + (x2-x1)^2)
Where (x1,y1) and (x2,y2) are the two points.
(–9, 0) and (2, 5).
Substituting into the equation
d = sqrt( (5-0)^2 + (2- -9)^2)
d = sqrt( ( 5^2 + (2+9)^2)
sqrt( ( 5^2 + (11)^2)
= sqrt( 25+121)
= sqrt( 146)
The distance between the two points is sqrt(74)
Final answer:
The distance between the points (–9, 0) and (2, 5) in the Cartesian plane is approximately [tex]\sqrt{146}[/tex] units.
Explanation:
To find the distance between two points in the Cartesian plane, we can use the distance formula.
The distance formula is:
distance = [tex]\sqrt{((x_2 - x_1)^2 + (y_2 - y_1)^2)}[/tex]
Using the given points (–9, 0) and (2, 5), we can plug in the values:
distance = [tex]\sqrt{((2 - (-9))^2 + (5 - 0)^2)}[/tex]
distance = [tex]\sqrt{((11)^2 + (5)^2)}[/tex]
distance = [tex]\sqrt{(121 + 25)}[/tex]
distance = [tex]\sqrt{146}[/tex]
So, the distance between the points (–9, 0) and (2, 5) is approximately [tex]\sqrt{146}[/tex] units.
What is the y-value of the vertex of the function f(x)=-(x-3)(x+11)
so, this is a quadratic equation, meaning two solutions, and we have a factored form of it, meaning you can get the solutions by simply zeroing out the f(x).
[tex]\bf \stackrel{f(x)}{0}=-(x-3)(x+11)\implies 0=(x-3)(x+11)\implies x= \begin{cases} 3\\ -11 \end{cases} \\\\\\ \boxed{-11}\stackrel{\textit{\large 7 units}}{\rule[0.35em]{10em}{0.25pt}}-4\stackrel{\textit{\large 7 units}}{\rule[0.35em]{10em}{0.25pt}}\boxed{3}[/tex]
so the zeros/solutions are at x = 3 and x = -11, now, bearing in mind the vertex will be half-way between those two, checking the number line, that midpoint will be at x = -4, so the vertex is right there, well, what's f(x) when x = -4?
[tex]\bf f(-4)=-(-4-3)(-4+11)\implies f(-4)=7(7)\implies f(-4)=49 \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill \stackrel{vertex}{(-4~~,~~49)}~\hfill[/tex]
Which expression is equivalent to (4 ^5/4 times 4^1/2 divided by 4^1/2)
Answer:
[tex] 2 ^ { \frac { 5 } { 2 } [/tex]
Step-by-step explanation:
We are given the following expression which we are to find its simplest form:
[tex] \frac { 4 ^ { \frac { 5 } { 4 } } \times 4 ^ { \frac { 1 } { 2 } } } { 4 ^ { \frac { 1 } { 2 } } }[/tex]
Cancelling the like terms to get:
[tex] 4 ^ { \frac { 5 } { 4 } } [/tex]
[tex] 2 ^ { 2 .\frac { 5 } { 4 } } = 2 ^ { \frac { 5 } { 2 } } [/tex]
[tex] 2 ^ { \frac { 5 } { 2 } [/tex]
Answer:
B
Step-by-step explanation:
If you are given the graph of h(x)=log(6)x, how could you graph m(x)=log(6)(x+3)? Translate each point of the graph of h(x) 3 units up. Translate each point of the graph of h(x) 3 units down. Translate each point of the graph of h(x) 3 units right. Translate each point of the graph of h(x) 3 units left.
Answer:
Last option: Translate each point of the graph of h(x) 3 units left.
Step-by-step explanation:
There are some transformations for a function f(x). The following is one of these transformations:
If [tex]f(x+k)[/tex], then the function is shifted "k" units to the left.
Given the function [tex]h(x)=log_6(x)[/tex] and the function [tex]m(x)=log_6(x+3)[/tex], you can notice that the function m(x) is the function h(x) but shifted left 3 units.
Therefore, you could graph the function m(x) by translating each point of the graph of the function h(x) 3 units left.
This matches with the last option.
Answer:
Last option (D) Translate each point of the graph of h(x) 3 units left.
Regular hexagon FGHIJK shares a common center with square ABCD on a coordinate plane. || . Across which lines can the combined figure reflect onto itself? A. any of the perpendicular bisectors of the sides of the hexagon B. either diagonal of the square C. any of the perpendicular bisectors of the sides of the square D. there are no lines across which this figure can reflect onto itself
Answer:
(C) Any of the perpendicular bisectors of the sides of the square
Step-by-step explanation:
In Regular Hexagon FGHIJK, we have 6 line of reflection across which the hexagon reflects onto itself. Those lines are:
3 perpendicular bisectors of sides i.e. perpendicular bisector of IJ , IH and GH
3 lines passing through vertices i.e. HK, IF and GJ.
While in Square, we have 4 line of reflection across which the square reflects onto itself. Those lines are:
2 perpendicular bisectors of sides AB and BC i.e. HK and perpendicular bisector of CD
2 digonals of square i.e. AC and BD
Also from figure we know that perpendicular bisector of CD and perpendicular bisector of IJ is the same line.
So, for combined figure we have to take common lines from both figures i.e. perpendicular of sides CD or IJ and line HK.
Answer:
Answer C
Step-by-step explanation:
Edmentum
Hook me up with a 5 star and a Thanks
x2 + 2x2 + 3x + 6
Factor
Answer:
See Below.
Step-by-step explanation:
I'm going to take the equation to be
y = x3 + 2x2 + 3x + 6
That is, the first term is a typo
make 2 groups. Put brackets around both groups.
group 1: x^3 + 2x^2 Take out the common factor of x^2
group 1: x^2(x + 2)
group 2: 3x + 6 Take out the common factor of x^2
group 2: 3(x + 2)
Now put the two groups together
Cubic = group 1 + group 2
Cubic = x^2 (x + 2) + 3(x + 2)
Now take out the common factor of x + 2
Cubic = (x + 2) (x^2 + 3)
8 lbs of cashew nuts cost $32. What is the cost of one pound?
Answer:
$4 per pound
Step-by-step explanation:
To find how much one pound of cashew nuts cost you have to use money over unit.
So money/unit, in this problem the money is 32 and the unit is 8.
So 32/8, now you divide 32 by 8 to get the price for one pound.
32 divided by 8 is 4
So $4 per pound
Answer:
The total cost of one pound is $4.
Step-by-step explanation:
[tex]\Large\textnormal{First, you divide the numbers from left to right to find the answer.}[/tex]
[tex]\displaystyle 32\div8=4[/tex]
[tex]\displaystyle \frac{8}{8}=1[/tex]
[tex]32\div4=8[/tex]
[tex]\displaystyle \frac{32}{8}=4\times1=4[/tex]
[tex]\Large \boxed{4}[/tex], is the correct answer.
I hope this helps you and have a wonderful day!
How to solve 3,4 and 6
Answer:
[tex]\large\boxed{3.\ V\approx130.88\ m^3}\\\boxed{4.\ V\approx35.21}\\\boxed{6.\ V\approx1.06\ in^3}[/tex]
Step-by-step explanation:
3.
The formula of a volume of a sphere:
[tex]V=\dfrac{4}{3}\pi R^3[/tex]
R - radius
We have R = 3.15 m. Substitute:
[tex]V=\dfrac{4}{3}\pi(3.15)^3\approx\dfrac{4}{3}\pi(31.26)\approx\dfrac{4}{3}(3.14)(31.26)\approx130.88\ m^3[/tex]
4.
The formula of a volume of a cone:
[tex]V=\dfrac{1}{3}\pi r^2H[/tex]
r - radius
H - height
We have 2r = 11.6 → r = 5.8 and H = x. Substitute:
[tex]V=\dfrac{1}{3}\pi(5.8)^2(x)=\dfrac{1}{3}\pi(33.64)x\approx\dfrac{1}{3}(3.14)(33.64)x\approx35.21[/tex]
6.
The formula of a volume of a cube:
[tex]V=s^3[/tex]
s - edge
We have s = 1.02 in. Substitute:
[tex]V=(1.02)^3\approx1.06\ in^3[/tex]
an app on your phone can estimate your time of arrival when given distance covered. You have travelled 4 1 2 kilometres. The app only accepts improper fractions.
Answer:
?
Step-by-step explanation:
wait is the kilometers number 412 or 41.2?
The mixed fraction 4 1/2 can be converted to the improper fraction 9/2 by multiplying the whole number by the denominator and then adding the numerator.
Explanation:The question is asking you to convert a mixed fraction (4 1/2) into an improper fraction. In your case of 4 1/2, an improper fraction is a fraction where the numerator (the top number) is greater than the denominator (the bottom number). To convert a mixed number into an improper fraction, you multiply the whole number (4) by the denominator of the fractional part (2) and add the numerator of the fractional part (1). This gives you the numerator of the improper fraction.
Here's how you do it: 4*2 = 8, then add 1, which gives you 9. Your improper fraction is thus 9/2.
Learn more about Improper Fractionhttps://brainly.com/question/19318336
#SPJ12
1,547.489 which digit is in the ten place
1,547.489
4 - Bold and underline one above is in the ten place.
Answer:
1,547.489
Step-by-step explanation:
Note that there is a decimal point in between 7 & 4, and the numbers to the left are whole numbers, while the numbers to the right is part of the decimal.
From the decimal point, count to the left two place value (to find the tens place):
1,547
1,547
4 is your digit in the ten's place, & is your answer.
~
All of the following are equivalent except___. 7x^3,4x+3x,(4+3)x,7x
Answer:
The one that is not equivalent is 7x^3
Step-by-step explanation:
7x^3= 7 * x*x*x
4x+3x = 7x = 7*x
(4+3)x = (7)x = 7*x
7x= 7*x
Answer:
7x^3
Step-by-step explanation:
All of the following are equivalent except 7x^3.
7x^3 = 7x^3
4x+3x = 7x
(4+3)x = 7x
7x = 7x